Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Sekretariat Dinas Lingkungan Hidup Dan Kehutanan D. I. Yogyakarta - Wilis Fahlefi; Suliantoro Suliantoro; Dedy Fatchurohim (Nur Science Institute, 2022)
This study aims to determine the influence of the work environment on employee performance at the Secretariat of the Environment and Forestry Service of D.I.Yogyakarta. The sample used in this study was to use the total sampling method or all employees at the Secretariat of the D.I.Yogyakarta Environment and Forestry Service with a population of 35 employees. The data collection technique is to distribute questionnaires. Data analysis using simple linear regression, based on the results of the study, the conclusion is that the work environment has a positive and significant effect on employee performance at the Secretariat of the Environment and Forestry Service, D.I.Yogyakarta.